Leczenie chirurgiczne czerniaka naczyniówki - Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The aim of this paper, was to report my own experiences of the surgical treatment of choroidal melanoma. 10 patients treated by transscleral resection with additional rutenium brachytherapy between January 1995 and June 2001, were evaluated in the study. Intraoperative complications included bleeding (3 cases), vitreous loss (3) and residual tumor successfully treated with iodine brachytherapy in one case. Postoperative retinal detachment with painful hypotony in one case was the reason of enucleation. The evaluation of functional results has shown no impairment of visual acuity in 20% of cases and did not change during follow up. These observations encouraged us in our belief that transscleral resection is an alternative method of treatment of choroidal melanoma.